Determinants of integrated soil fertility management technologies adoption by smallholder farmers in the Chinyanja Triangle of Southern Africa. (31st December 2016) - Mponela, Powell; Tamene, Lulseged; Ndengu, Gift; Magreta, Ruth; Kihara, Job; Mango, Nelson
Graphical abstract: Highlights: Farmers in Chinyanja Triangle (Southern Africa) are financially constrained but potentially resourceful. ISFM adoption is clustered into technological sets with complementary outcomes. The choice for a set of technologies vary by inherent technological features and is also contextual. Abstract: Integrated Soil Fertility Management (ISFM) technologies have proven to be viable options for improving land productivity and increasing yield. However, adoption of the set of complementary technologies that are required in ISFM is quite variable and studies tend to focus on single technologies. In this study we used cluster analysis to group technologies and ordered probit to determine the probability of multiple technology adoption. The result show that usage of ISFM in the Chinyanja Triangle (Southern Africa) is grouped into 3 technological sets based on complementarities. The set of nutrient dense technologies of inorganic fertiliser, compost and animal manure (ISFMset3) indicates that they are used by farmers who face similar opportunities of having land that require minimal input, sell produce at farm gate as opposed to market, have more transport and communication facilities, and recover from livestock loss. Loss of crops, however, deter adoption of this set. The technological set comprising of fallow, rotation and grain legumes (ISFMset2) which enhances biomass accumulation and nitrogen fixation with complementary effects in cereal dominated farming system, is more likely adopted by households with land that require more inputs, are more educated, own more bicycles and have higher financial capital. Other four technologies (ISFMset1 including mulch, lime, compost and agroforestry) are used by a few individuals to address specific constraints in nutrient and water retention, and acidity. The result also indicated variations in usage of ISFMset3 between sites. These results are instrumental in identifying factors that influence adoption of a set of ISFM technologies in the Chinyanja Triangle and could be of use in targeting research and development initiatives.